1994
DOI: 10.1046/j.1365-2648.1994.20060997.x
|View full text |Cite
|
Sign up to set email alerts
|

Staff nurses' work satisfaction in psychogeriatric wards

Abstract: This paper begins by reviewing the small number of studies of staff nurses' work satisfaction. Subsequently, an examination is made of the differences in work satisfaction between staff nurses and other grades of nursing staff in psychogeriatric wards in National Health Service hospitals in Scotland. These data are part of a larger study into work satisfaction and the quality of care in these settings. Significant differences in satisfaction at work are identified between the staff nurse group and the other gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 11 publications
3
9
0
Order By: Relevance
“…(2004) report that nurses working in long‐term care settings were more dissatisfied than those who worked outside long‐term care settings caring for similar categories of patient. Similar to this study, the nursing literature reports the existence of a negative relationship between nurses level of job satisfaction and routine (Blegen & Mueller 1987, Giloran et al . 1994).…”
Section: Discussionsupporting
confidence: 83%
“…(2004) report that nurses working in long‐term care settings were more dissatisfied than those who worked outside long‐term care settings caring for similar categories of patient. Similar to this study, the nursing literature reports the existence of a negative relationship between nurses level of job satisfaction and routine (Blegen & Mueller 1987, Giloran et al . 1994).…”
Section: Discussionsupporting
confidence: 83%
“…These findings are supported by those of a study conducted by Gilloran et al . (1994) , who revealed that nurses were frustrated with supervision of their work in a psycho‐geriatric unit.…”
Section: Themes Revealed By the Analysis Of Datasupporting
confidence: 91%
“…Elovainio & Sinervo (1997) suggest that of all professional groups in social welfare and health care, state enrolled nurses experience most strain. Gilloran et al . (1994 ) maintain that staff working with patients with chronic conditions are frustrated with their work.…”
Section: Literature Reviewmentioning
confidence: 99%